استخدام الباحثين للمكتبات الجامعية مقارنة بالإنترنت: المكتبة المركزية لجامعة بغداد - الوزيرية انموذجا - صالح، منى هادي (الجامعة المستنصرية - كلية التربية الأساسية, 2017)
يهدف البحث إلى التعرف على مدى استخدام المستفيدين للمكتبة المركزية لجامعة بغداد/الوزيرية مقارنة بالانترنت في البحث عن مصادر المعلومات، والتحقق من مستويات استفادة المستفيدين من المكتبة المركزية لجامعة بغداد والإنترنت، استخدام المنهج المسحي، واعتمدت استبانة وزعت على عينة البحث المتكونة من أعضاء الهيئة التدريسية وطلبة الدراسات العليا، وطلبة الدراسات الأولية. توصل البحث إلى جملة استنتاجات منها: 1. يتفق أغلب المستفيدين أن أهم المعوقات التي يواجهونها من استخدام المكتبة المركزية لجامعة بغداد/ الوزيرية هي أن الملاك الوظيفي لا يقدم لهم المساعدة في بحثهم عن المعلومات التي يحتاجونها غالبا. 2. أن مجموعة المكتبة المركزية لجامعة بغداد/ الوزيرية لا تلبي الاحتياجات البحثية للمستفيدين منها وذلك بسبب عدم شموليتها وافتقارها للحداثة. 3. إن بعض المواقع الموجودة على شبكة الإنترنت توفر معلومات ببليوغرافية فقط عن المصادر ولا تتيح إمكانية تحميل النص الكامل للمصدر إلا مقابل دفع مبالغ مادية للحصول على المصدر المطلوب. 4. من معوقات استخدام الإنترنت هي أن بعض المعلومات المنشورة على الإنترنت لا تمتاز بالموثوقية. أما أهم المقترحات التي تم وضعها في البحث فكانت كالآتي: - 1. ضرورة قيام اللجنة المعنية بتوفير المصادر الأخذ بنظر الاعتبار احتياجات المستفيدين وتوفير المجموعة التي تلبي الاحتياجات البحثية للمستفيدين منه مع توفير عنصر الحداثة والشمولية للمصادر. 2. تحقيق نوع من السيطرة والضبط للمواقع المتاحة على الإنترنت لتوفير المعلومات الموثوقة وضرورة توفير النصوص الكاملة للمواقع التي تقوم بتوفير المعلومات الببليوغرافية للمصادر. The purpose of the research is to identify the extent to which beneficiaries have used the central library of the University of Baghdad / Al-Waziriya compared to the Internet in searching for sources of information and verifying the levels of benefit of the users of the Central University of Baghdad University and the Internet. The survey method was used and a questionnaire was distributed to the research sample, Teaching and graduate students and students of preliminary studies. The research reached a number of conclusions, including : 1. Most of the beneficiaries agree that the main obstacles they face from using the central library of the University of Baghdad / Waziriya are that the staff does not provide them with assistance in their search for the information they often need. 2 - The central library collection of the University of Baghdad / Waziriya does not meet the research needs of the beneficiaries because of lack of comprehensiveness and lack of modernity. 3 - Some sites on the Internet provide bibliographical information only about the sources and does not allow the possibility to download the full text of the source only for payment of material amounts to obtain the required source. 4. One of the obstacles to using the Internet is that some information published on the Internet is not reliable. The most important proposals that were put in the research were as follows: 1 - The need for the Committee to provide resources to take into account the needs of beneficiaries and provide a group that meet the research needs of beneficiaries, while providing the element of modernity and comprehensiveness of resources. 2 - To achieve some kind of control and control of the sites available on the Internet to provide reliable information and the need to provide full texts of the sites that provide bibliographic information for sources.
Keywords: المكتبات الجامعية -- الاحتياجات البحثية -- مصادر المعلومات -- شبكات الإنترنت -- جامعة بغداد